Distance and Intimacy: Reading The Woman of Colour (1808) with Hazel V. Carby’s Imperial Intimacies (2019) - Wassif, Mariam (Romanticism on the Net)

(untitled) (Université de Montréal, 2024)
This essay argues that both the anonymously authored novel The Woman of Colour (1808) and Hazel V. Carby’s memoir Imperial Intimacies (2019) telescope back and forth from the most intimate domains of family—especially motherhood—to the vast expanses of Britain’s global empire. They can be described, as Edward Said writes of Mansfield Park, as "very precisely about a series of both small and large dislocations and relocations in space,” but instead of finding themselves “spiritual mistresse[s]” of the home by the end of the narrative, Carby and Olivia, the protagonist of The Woman of Colour, remain mobile in ways that emphasize the instabilities and shifting forms of imperial relations. For Olivia and Carby, home is not the enduring English country house whose fate is secured through heterosexual marriage, as in Mansfield Park. Rather, it is everywhere and nowhere, a set of relationships that are continuously negotiated across centuries and continents, in the context of perpetual transit. Furthermore, when read together, Imperial Intimacies and The Woman of Colour illuminate how racialized femininity, as it intersects with motherhood, is at once a cornerstone and a problem of empire.